Effects of Inhibition or Deletion of PCSK9 (Proprotein Convertase Subtilisin/Kexin Type 9) on Intracerebral Hemorrhage Volumes in Mice. Issue 11 (November 2020) - Schlunk, Frieder; Fischer, Paul; Princen, Hans M.G.; Rex, Andre; Prinz, Vincent; Foddis, Marco; Lütjohann, Dieter; Laufs, Ulrich; Endres, Matthias
Abstract : Supplemental Digital Content is available in the text.